Afrobixas : narrativas de negros homossexuais sobre seu lugar na sociedade - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The general objective of this work is to unveil meanings and formative implications that emerge from the life histories of the constituent subjects in the identity intersection between blackness and homosexuality. To achieve this, the research is developed within the assumptions of the qualitative nature and proposes the adoption of the phenomenological method (SANDERS, 1982; RIBEIRO JUNIOR, 2003; MOREIRA, 2004), based on the ‘open interview’ and the ‘(auto)biographical narratives’ (LÜDKE; ANDRÉ, 1986; JOSSO, 2004; CHIZZOTTI, 2011) of five members of the Coletivo Afrobixas, as research tools for the composition of the methodological corpus. The theoretical contribution refers to the discussions about black ethnic-racial relations (BRASIL 2004a; GOMES, 2005a) and homosexuality (MARSIAJ, 2003; MISKOLCI, 2007; 2015; LOURO, 2015), in order to relate such discussion with the deconstruction of the Western hegemonic meanings of human formation (CAMBI, 1999; FERRAREZI JÚNIOR, 2014; ABBAGNANO, 2007). At this point, the establishment of problematizations regarding the Eurocentric and heteronormative basis this formation (GOMES, 2005; NASCIMENTO, 2003; QUIJANO, 2005; MOORE, 2010; BUTLER, 2003; FOUCAULT, 2014) of can be found in the critical and revolutionary aspects of multiculturalismo (MCLAREN, 2000; ALBUQUERQUE; BRANDIM, 2008; CANDAU, 2008; 2011), in studies about the relationship between sexual minorities, education, sexual rights and prejudices (BORRILLO, 2010; VECCHIATTI, 2012; LINS; MACHADO; ESCOURA, 2016), as well as in the intersectional approaches that involve factors such as social class, race, gender and sexuality (CRENSHAW, 1989; ANZALDÚA, 1999; BRAH; PHOENIX, 2004; LORDE, 2009; hooks, 2013). The interpretations of the narratives generated by the participants show that their formative and informal formative experiences have been guided by factors that are beyond the identity categories of blackness or homosexuality, correlating in multidimensional and intersectional aspects constituted by racial, gender, social class and sexual orientation, which have been permeated by social oppression such as racism and homophobia. In addition, the participation of the narrators in the Coletivo Afrobixas suggests that the experiences in this grouping contribute to the (res)significance of their excentric identities through critical reflection on the normalization of socially hegemonic models and values or through the encouragement provided by their awareness and their personal and collective empowerment, in order to redefine the importance of their place and contribution in society.
Keywords: Negritude; Homossexualidade; Interseccionalidade; Narrativas (auto)biográficas; Fenomenologia; Blackness; Homossexuality; Intersectionality; Authobiografical narratives; Phenomenology; CIENCIAS HUMANAS::SOCIOLOGIA